Inflammation is associated with the presence and severity of chronic coronary syndrome through soluble CD40 ligand - Pereira-da-Silva, Tiago (2021)
This study is part of the PhD thesis program of one of the authors (TPdS), supervised (MMC) and co-supervised (PN) by other two, conducted in NOVA Medical School/Faculdade de Ciências Médicas, Universidade NOVA de Lisboa, Lisbon, Portugal. TP acknowledges the support of Fundação para a Ciência e Tecnologia, Portugal (Project UID/BIO/04565/ 2020), and Programa Operacional Regional de Lisboa 2020 (Project N. 007317). The authors are grateful to Joana Castro, PhD, from Medinres - Medical Information and Research, for her advice in the statistical analysis.